859 Occupational exposure to acephate among oil palm plantation workers: glove permeation study. (24th April 2018) - Ismail, I; Roslan, MNF; Saharuddin, MIS; KAM, Isa
Abstract : Introduction: Spills or splash during mixing, loading and application organophosphate insecticide may entail significant dermal exposure to agricultural workers. Although gloves are religiously worn, the level of chemical protection afforded by these gloves is unclear. In this study, the influence of exposure temperature and duration on glove permeation were investigated for acephate, an organophosphate insecticide used for trunk injection on oil palm trees. Potential contamination on the skin of the workers was also investigated. Methods: Nitrile gloves used by oil palm plantation workers during trunk injection were tested at room temperature and elevated temperature (45°C), using standard permeation cells. Skin wipe samples were collected from the face and hands of the workers to examine whether acephate still contaminated their skin. Chemicals analysis was via HPLC-UV. Results: Higher maximum flux and greater cumulative permeation of acephate were observed over the 4 hour exposure period. Gloves with 5% simulated abrasion showed reduced performance compared to new gloves. Contamination on the face and hands of the workers were minimal. Conclusion: Limited protection is provided by gloves, even for diluted acephate, especially at 45°C. The findings indicate the need for more suitable gloves, with frequent change, especially when working in warmer conditions and where abrasion is observed on the gloves. While workers behaviour was good, emphasis on the correct techniques of glove removal may assist in avoiding transfer of contaminants.